New chemical elements dynamic synthesis in ultra-deep penetration zones - Ju. S. Usherenko; S. M. Usherenko; A. H. Jazdani Cherati (Литьë и металлургия)
It is shown that synthesized rare–earth elements – lanthanum and cerium – were detected as a result of the effect of the ultra‑deep penetration process (SDP) on the welding zone of two steel plates. When moving in the welding zone of clumps of microparticles, channels are formed where fibers are formed, in which new chemical elements from the group of rare earth metals – lanthanum and cerium – are synthesized due to additional energy.